2013
DOI: 10.1002/jcc.23490
|View full text |Cite
|
Sign up to set email alerts
|

Net charge changes in the calculation of relative ligand-binding free energies via classical atomistic molecular dynamics simulation

Abstract: The calculation of binding free energies of charged species to a target molecule is a frequently encountered problem in molecular dynamics studies of (bio-)chemical thermodynamics. Many important endogenous receptor-binding molecules, enzyme substrates, or drug molecules have a nonzero net charge. Absolute binding free energies, as well as binding free energies relative to another molecule with a different net charge will be affected by artifacts due to the used effective electrostatic interaction function and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 97 publications
0
112
0
Order By: Relevance
“…As noted previously, mutations in which the net charge of the system is changed present significantly greater difficulties for FEP simulations due to periodic boundary condition artifacts, as has been investigated by Parameswaran et al and Rocklin et al [27], [28], Lin and coworkers [41], and Reif and Oostenbrink [42]. These authors have suggested a posteriori corrections using Poisson–Boltzmann (PB) electrostatics to ameliorate these problems, a technique that appears to be promising.…”
Section: Discussionmentioning
confidence: 96%
“…As noted previously, mutations in which the net charge of the system is changed present significantly greater difficulties for FEP simulations due to periodic boundary condition artifacts, as has been investigated by Parameswaran et al and Rocklin et al [27], [28], Lin and coworkers [41], and Reif and Oostenbrink [42]. These authors have suggested a posteriori corrections using Poisson–Boltzmann (PB) electrostatics to ameliorate these problems, a technique that appears to be promising.…”
Section: Discussionmentioning
confidence: 96%
“…This is based on the work by Reif and Oostenbrink [21], Rocklin et al [22], and earlier work from Kastenholz and Hünenberger [23, 24]. Here corrections on the free energy estimation for a BWRF atom based cutoff for the discharging step were derived.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Here corrections on the free energy estimation for a BWRF atom based cutoff for the discharging step were derived. Net charge free energy calculations are affected by several finite size artefacts [21, 22]. To be computationally efficient periodic boundary conditions along with an effective Coulombic potential are employed, which introduces artefacts that can be sizable for simulations of charged species [25, 26].…”
Section: Theory and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a widely known and well-understood problem of simulations with a lattice-sum electrostatic interaction function [18, 35, 58, 63, 65, 67, 69, 70, 81, 82]. There is a second issue that is not reflected in structural properties but only in thermodynamic properties.…”
Section: Theorymentioning
confidence: 99%